Ecological Retaining Wall for High-Steep Slopes: A Case Study in the Ji-Lai Expressway, Eastern China - Peng Jiang; Jin Li; Shen Zuo; Xin Zhuang Cui (Advances in Civil Engineering)
Research on the retaining structures for high-steep slopes is extremely significant because of its real-world applications and far-reaching implications. A flexible geocell-reinforced ecological retaining wall as a high-steep slope protection scheme was developed and applied to the slope protection project of the Ji-Lai Expressway by analyzing the reinforcement mechanism of the geocell used. The lateral displacement and Earth pressure distribution on the flexible ecological retaining wall applied to the high-steep slope were studied using finite element numerical simulations and verified using field experiments. Results reveal that the wall maximum horizontal displacement is 2/3 H away from the wall toe because of the replacement of the upper part of soil. There is an obvious bucking effect on the active Earth pressure around the stiffened site, and the flexible deformation of the retaining wall helped effectively release some of the Earth pressure. Consequently, the measured value is lower than the theoretical value. Through this case study, it is demonstrated that the flexible ecological retaining wall as a slope protection technology can be successfully applied to steep slopes with a height of more than 15 m. Moreover, it brings significant advantages for protecting the ecological environment and improving the highway landscape.